Pemberian Madu Sebelum Tidur terhadap Pemenuhan Kebutuhan Tidur Lansia - I Gusti Ayu Ari Rasdini (Jurnal Gema Keperawatan, 2013)
This research aimed to know the effect of honey giving before sleep to the elderly needs fulfillment. This research were pre-experimental research design by using one group pre-post test design. The number of samples were 32 respondents in nonprobability with purposive sampling. Data analysis techniques which used to test the hypothesis that were Paired-Sample T-Test with significancy level of 5% (0.05). The results of research showed the average of fulfillment of the sleep needs before given honey were 12.5 and after were 9.4 so that obtained an average improvement of sleep needs fulfillment before and after giving honey that were 3.1. P-value = 0.000 its means that p 0.05 so that Ho is rejected, then it can be stated that there was significant effect of giving honey before sleep in the elderly in the PSTW Wana Seraya Denpasar.